Surgical Correction of Articular Damage in the Knee: Osteoarticular Transplantation to Joint Reconstruction - Bai, Xue Susan; Thomas, Jonelle M.; Ha, Alice S. (Seminars in Musculoskeletal Radiology, 2017)
Injuries of the articular cartilage remain difficult to treat and can range from small articular cartilage defects to end-stage severe osteoarthritis. In this review, we discuss various surgical treatment options including imaging features and associated complications. Specifically, we review microfracture, acellular matrix-induced microfracture, autologous osteochondral transplantation, osteochondral allograft transplantation, autologous chondrocyte implantation, along with various forms of knee arthroplasties.
Keywords: osteochondral lesion; total knee arthroplasty; autologous osteochondral transplantation; osteochondral allograft transplantation